LCH with Multisystemic Involvement-A Case Report - Sehgal, Shreya; Maralakunte, Muniraju; Singh, Lokesh; Debi, Uma (Archives of Clinical and Medical Case Reports, 2021)
Langerhans cell histiocytosis (LCH) constitutes a rare group of disorder derived from the macrophages and dendritic cells. The cells in LCH show close similarity to the langerhans cells found in the skin and mucosa and stain positive for CD1a, S100, and CD207 antigens. These cells display the same intracytoplasmic organelles on electron microscopy as seen in Langerhans cells i.e. Birbeck granules. LCH is ten times more prevalent in the paediatric age group as compared to adult population. Females are affected more commonly as compared to the males. LCH can have single- or multi-system types of involvement. Unifocal or multifocal pattern is seen in singlesystem type of disease. The multisystem pattern is often seen in the paediatric population while unisystem pattern is seen in adults. We present case report of a 35 yrs old male patient with multisystemic involvement.